2013
DOI: 10.1002/aic.14155
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of subgrid drag modifications for dense gas‐particle flows in bubbling fluidized beds

Abstract: Many subgrid drag modifications have been put forth to account for the effect of small unresolved scales on the resolved mesoscales in dense gas‐particle flows. These subgrid drag modifications significantly differ in terms of their dependencies on the void fraction and the particle slip velocity. We, therefore, compare the hydrodynamics of a three‐dimensional bubbling fluidized bed computed on a coarse grid using the drag correlations of the groups of (i) EMMS, (ii) Kuipers, (iii) Sundaresan, (iv) Simonin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
101
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 109 publications
7
101
2
Order By: Relevance
“…simulations using the cylindrical grid 18 × 120 × 12 (say, for the bubbling fluidization case) be compared with the Cartesian grid 15 × 120 × 15 (note: 15 diametrical cells). However, with this cross-sectional resolution, the resulting Cartesian grid is too coarse (25 times the particle diameter) and hence, cannot predict the hydrodynamics accurately [35,39]. On the other hand, a Cartesian grid with identical cross-sectional resolution as the cylindrical radial grid may be used, i.e.…”
Section: Resolution Study and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…simulations using the cylindrical grid 18 × 120 × 12 (say, for the bubbling fluidization case) be compared with the Cartesian grid 15 × 120 × 15 (note: 15 diametrical cells). However, with this cross-sectional resolution, the resulting Cartesian grid is too coarse (25 times the particle diameter) and hence, cannot predict the hydrodynamics accurately [35,39]. On the other hand, a Cartesian grid with identical cross-sectional resolution as the cylindrical radial grid may be used, i.e.…”
Section: Resolution Study and Validationmentioning
confidence: 99%
“…The application of an appropriate centerline treatment, though, is still imperative and numerically, it particularly affects the computation of the diffusion and drag force terms in the cells at the grid center. Thus, using an accurate centerline condition is not only essential for understanding the hydrodynamics of more complex flows (eg mixtures, reactive flows) but also for constructing accurate sub-grid models for coarse grid simulations [33][34][35]. Recently, Verma et al [28] simulated solid-gas fluidization in a cylindrical bed using a similar approach and predicted the radial velocity using diametrical momentum averaging.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a procedure inevitably neglects small (unresolved) scales, which leads, for example, to a considerable overestimation of the bed expansion in the case of fine particles. Many sub-grid drag modifications have, therefore, been put forth by academic researchers to account for the effect of small unresolved scales on the resolved meso-scales in this case [2,3,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of such a modeling strategy is to use a combination of a Lagrangian discrete phase model (DPM) and a coarse-grained TFM to take advantage of the benefits of those two different formulations. Furthermore, sub-grid drag corrections [2][3][4] are applied to account for the impact of the small unresolved scales on the gas-solid drag force. As in our earlier studies [4,6] we use a coarse-grained kinetic-theory based two-fluid model to study fluidization.…”
Section: Introductionmentioning
confidence: 99%
“…The model has also been subjected to extensive tests from outside and to various modifications to meet the requirements of the specific problems they studied. It has been modified (i) to simulate CFB combustors [114,115], calcium looping for CO 2 capture in a lignite fired power plant [116], CFB carbonator [117] and gas desulfurization in a CFB riser [118]; (ii) to address the anisotropic characteristics of EMMS drag model [119]; (iii) to test the effects of using different particle cluster size correlations [120,121]; (iv) to model the effective interphase drag force of bubbling fluidization [122][123][124]; (v) to formulate an EMMS drag model that is conceptually consistent with the so-called type A two-fluid model and its applications [125][126][127][128][129][130]; (iv) to formulate another version by assuming the particle in dilute phases are in dilute limit and the particles in dense phase satisfy the Richardson-Zaki correlation [131,132]. Recent studies have shown that the EMMS drag model can also be used in Eulerian-Lagrangian simulations [133][134][135][136][137].…”
mentioning
confidence: 99%